Eclipse (2016), volume 3 ebook - Kaplan, Zack (Eclipse (2016), 2019)
In a world where sunlight is deadly, a corporate heiress-turned-rebel, her corrupt solar tycoon father, and a former hero seeking redemption, all find themselves battling to find and control the mysterious Scientist responsible for an immunity to dangerous sunlighta Scientist with his own plans in mind. Collects ECLIPSE #9-12. Author: Zack Kaplan. Illustrator: Giovanni Timpano . 2019 Top Cow Productions, Inc.